Effect of Internal and External Attention with / without motivational music Training on Dynamic Balance Task - Gholam Hossein Nazemzadegan; Roghayeh Eider (University of Tehran, 2015)
The aim of this study was to determine the effects of external attention (EA) and internal attention (IA) with & without motivational music training on dynamic balance task. The method was quasi-experimental and the sample involved 60 athletic maile who were volunteers to participate in this study. After pre-test, Subjects were divided into 5 groups of 12 members randomly. Groups were: IA with music, EA with music, IA without music, EA without music and Control. This research conduct with 3 phase. First, Pre-test. In 2nd, Subjects were doing exercise protocol in 3 consecutive days in phase for groups with music in addition attentional strategies, motivational music play by CD. 3nd was post -test in According to of research design, if music had could significant effect on performance after variable using, then in  4th phase, data can be Analyzed. ANOVA test do not show significant difference among groups. In other words, (EA) and (IA), strategies with / without music cannot affect on balance ability. The significance level in this research was α= 0.05.